Antibacterial activity of Psidium guajava (guava) leaf extract against Xanthomonas oryzae pv. oryzae and Pseudomonas fuscovaginae - Paisol, Nur Afiqah Syahirah (2017)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae is one of the most important in disease of rice. The symptom usually established mainly on leaf blades, leaf sheath and sometimes on grains. Yellow water soaked lesions will appear on an infected leaves margin of its leaf blade. The lesion will appear parallel along the leaf and then will join together covering the whole leaf. Early in the morning, milky dew drop bacterial discharge will emerge on young lesion. The leaf then dries up with white lesions as the disease progress and the margin of the leaf blade will becomes wavy. Bacterial sheath brown rot shows symptom such as discoloration of the leaves and then spreaded to midrib or vein of the leaves. Brown necrotic lesion will be also visible from small to large. Usually, these diseases was managed through application of copper-based fungicide or bactericide. However, these chemical control has created environmental issues as well as problems to human health. Therefore, biological control is now emphasized as another strategy to control pathogens. This study was conducted to determine the antagonistic activity of guava leaf extract against Xanthomonas oryzae pv. oryzae and Pseudomonas fuscovaginae, determination of minimum inhibitory concentration and to determine the minimum bactericidal concentration of guava against Xanthomonas oryzae pv. oryzae and Pseudomonas fuscovaginae. Guava leaves were collected and extracted with two different solvents with different concentration to get the crude extract. Leaf extract was screened with Xanthomonas oryzae pv. oryzae and Pseudomonas fuscovaginae by using agar well diffusion method and result shows that, guava leaf extract can inhibit the growth of Xanthomonas oryzae pv. oryzae at minimum concentration of 50 mg/ml with 2.3833 means diameter of inhibition zone but cannot inhibit Pseudomonas fuscovaginae. Further experiment with minimum inhibitory concentration and minimum bactericidal concentration found out that the leaf extract can only make the Xanthomonas oryzae pv. oryzae in bacteriostatic state instead of inhibit the bacterial growth. Thus, guava extract have potential to be used as biological control to control bacterial leaf blight, but cannot be used to control brown sheath rot.